PENGARUH KEGIATAN OUTBOUND TERHADAP KEMANDIRIAN ANAK USIA 5-6 TAHUN DI TK PERTIWI KOTA PEKANBARU - Mestika Febiola; Zulkifli Zulkifli; Febrialismanto Febrialismanto (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: The study aims to determine the effect of outbound activities on the independence of children aged 5-6 years in Pertiwi TK Pekanbaru City. This research is an experimental research using one group design under pre-test by using an sheets of children's independence. The sample in this study were class B3 as many as 15. The method used is pre-experiment with one group desgn that is experiment conducted only in one group without any comparison group. The type of instrument used in this study was by utilizing an observation guidelines to record the activities that occurred during the given treatment. Based on hypothesis test results obtained that there wasan effect of outbound activities on the independence of children aged 5-6 years. Obtained t value of 19,972 with sig 0,00, due to sig <0,05, it can be concluded that there are significant differences in independence in students before and after the application of activities outbound. In hypothesis test can be seen t calculate = 19,972 > t table = 2,110. It can be interpreted that there are significant differences in results between pretest and posttest. The influence of outbound activities on the independence of children aged 5-6 years in Pertiwi City Pekanbaru is 35,43%Key words: Outbound Activities, Independence of Children